A Microseismic/Acoustic Emission Source Location Method Using Arrival Times of PS Waves for Unknown Velocity System - Longjun Dong; Xibing Li (International Journal of Distributed Sensor Networks)
To eliminate the location error of MS/AE (microseismic/acoustic emission) monitoring systems caused by the measurement deviations of the wave velocity, a MS/AE source location method using P-wave and S-wave arrivals for unknown velocity system (PSAFUVS) was developed. Arrival times of P-wave and S-wave were used to calculate and fit the MS/AE source location. The proposed method was validated by numerical experimentations. Results show that the proposed method without the need for a premeasured wave velocity has a reasonable and reliable precision. Effects of arrival errors on location accuracy were investigated, and it shows location errors enlarged rapidity with the increase of arrival errors. It is demonstrated the proposed method can not only locate the MS/AE source for unknown velocity system but also determine the real time PS waves velocities for each event in rockmass.